Assessing The Evolution Of Slum’s Urban Form In Chouf Lekdad, Setif From 2003 To 2023 - Naidja, Sarra; Daich, Safa (Journal of Architecture and environment of child, 2025)
Housing represents a significant problem in Algeria, characterized by enormous challenges. The phenomenon of informal housing has merged and rapidly worsened for many reasons. As a result, slums have become a prevalent form of informal housing, offering a living space for families with limited resources on the city’s outskirts. However, these informal settlements have grown over time, indicating an evolving informal urbanism and the emergence of a different urban form through the self-build and organisation of numerous houses. This study aims to assess the spatiotemporal distribution of informal housing in Setif, Algeria. Additionally, it seeks to analyse the evolution of the slum area to comprehend the urban form characteristics of this informal housing. It also assesses the factors and causes that influenced the development of this particular form. A combination of methodologies was used to attain the purpose of this study. It included in-situ observations and remote sensing to analyse the spatial distribution and temporal evolution of these informal settlements from 2003 to 2023 using Google Earth and GIS to map and visualise the changes, helping to identify their emerging form. This study investigated the Chouf Lekdad slum area in Setif, Algeria. This investigation determined that this slum’s area is entirely residential because it is based on individual needs. The spatial distribution was initially characterised by sparsely built-up areas, which gradually became denser in a particular part. Buildings and vacant space have similarities in shape and scale, harmoniously integrating into the overall form of the site. This organisation can allow other occupants to construct or enlarge their buildings. Therefore, it is challenging to accurately predict the amount and arrangement of potential empty space.